2020
DOI: 10.1111/jce.14439
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a novel active fixation quadripolar left ventricular lead for cardiac resynchronization therapy: Attain Stability Quad Clinical Study results

Abstract: Introduction: The Medtronic Attain Stability Quad lead is a quadripolar left ventricular (LV) lead with an active fixation helix assembly designed to fixate the lead within the coronary sinus and pace nonapical regions of the LV. The primary objective of this study was to determine the safety and effectiveness of this novel active fixation quadripolar LV lead.Methods: Patients with standard indications for cardiac resynchronization therapy (CRT) were enrolled. All patients were followed at 3 and 6 months post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 20 publications
3
20
0
Order By: Relevance
“…The Attain Stability Quad Clinical Study results also reported a high success rate of LV lead placement (96.8%) with a low dislodgement rate (0.7%). Furthermore, the success rate of placement in the prespecified target pacing location was 97%, and in 90.6% of them, a tip electrode was located in the non-apical region [6]. In the present case, the peripheral venous diameter of the lateral vein was sufficient for lead placement; however, pacing from the apical region was unavoidable when a conventional LV lead was used.…”
Section: Discussionmentioning
confidence: 59%
“…The Attain Stability Quad Clinical Study results also reported a high success rate of LV lead placement (96.8%) with a low dislodgement rate (0.7%). Furthermore, the success rate of placement in the prespecified target pacing location was 97%, and in 90.6% of them, a tip electrode was located in the non-apical region [6]. In the present case, the peripheral venous diameter of the lateral vein was sufficient for lead placement; however, pacing from the apical region was unavoidable when a conventional LV lead was used.…”
Section: Discussionmentioning
confidence: 59%
“…8 The Medtronic Attain Stability Quad lead, which combines an active fixation mechanism with a quadripolar lead, allows for a targeted approach to LV pacing. 3,9,10 Using an active fixation lead allows for better stability in the veins, which often have large diameters, compared with a passive fixation lead, the stability of which concerns operators. 11 It is also important to develop a technique to advance an LV lead through target vessels and to overcome lead stability issues.…”
Section: Discussionmentioning
confidence: 99%
“…The new location of the fixation helix between electrodes 3 and 4 in the Medtronic lead model 4798 may potentially further augment the stability of the active fixation lead. 18 There is an obvious concern about the extractability of active fixation LV lead. Unlike the leads with side lobes of the lead, the Attain Stability is fixated with a side helix constructed to uncoil in response to retractive force.…”
Section: Discussionmentioning
confidence: 99%
“…The present trial did not prove that adding an active fixation mechanism to bipolar lead makes them more stable than passive fixation quadripolar leads. The new location of the fixation helix between electrodes 3 and 4 in the Medtronic lead model 4798 may potentially further augment the stability of the active fixation lead 18 . There is an obvious concern about the extractability of active fixation LV lead.…”
Section: Discussionmentioning
confidence: 99%